Program Kemitraan Universitas bagi Pengurus Kelompok Tani Sumber Rejeki III untuk Mengelola Administrasi Keuangan Syariah - R Arri Widyanto; Sunarni Sunarni; Andi Triyanto (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2019)
Sumber Rejeki III Farmers Group is an organization that accommodates farmers in Turen, Kradenan Village. Currently there are 45 active members of farmer groups, all of whom are from Turen. The management of the average main job is farmers who are on average 48 years old. The level of education of the management of high school and equivalent farmer groups. The level of mastery of computer operations 0% of all managers. The problem that occurs in this farmer group is that there are no administrators who can operate the computer, so the administration has not been well organized. All documents are written manually using separate books and note papers. Especially in making reports of Lembaga Keuangan Mikro(LKM) that must be reported every month to farmer groups, they must collect from many records and not infrequently there are records that are scattered or lost which cause reports especially financial statements to be invalid. The objectives of this partnership program are: (a) Giving skills to operate computers, especially office application programs for farmer group administrators. (b) Giving skills in making invitations automatically using a mail merge facility. (c). Improve ability in recording and making financial reports. The methods used: (a) the preparation stage, (b) the implementation stage, (c) the evaluation phase and (d) preparing the report. The results of this activity, the average level of mastery of computer utilization for administrative activities are as follows: Mastering (0.78%) and Self-mastering (0.22%), Output of PKU is increasing the ability of partners to use computer applications for administration to 70% of the original target of 50%. In addition, savings and loan activities for these farmer groups' LKM use the sharia accounting system